2024
DOI: 10.1037/sah0000364
|View full text |Cite
|
Sign up to set email alerts
|

(Un)veiling distinct feelings: A typology of affective reactions while meeting people with facial disfigurement for the first time.

Abstract: This research aims to better understand the affective dimension in the public stigma of people with facial difference (FD) by identifying the perceivers’ various affective reactions to FD and by grouping them in a relevant typology. In a first qualitative step (N = 47), a vignette study based on a self-presentation paradigm was used to get participants to generate a comprehensive list of the affective states they may feel when they first meet people with FD. In a second quantitative step (N = 385), a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This is in contrast to the long standing “What is Beautiful is Good” bias ( Dion et al, 1972 ). From a recent study using fMRI, it appears that these negative responses are “hardwired” into the occipito-temporal cortex as well as anterior cingulate cortex of the brain ( Hartung et al, 2019 ), which may explain the particularly negative reactions that facial disfigurement illicits ( Stone and Potton, 2019 ; Rasset et al, 2022 ). Encouragingly, plastic surgical procedures that minimize disfigurement result in more positive perceptions of individuals with disfigurement ( Mazzaferro et al, 2017 ; Jamrozik et al, 2019 ).…”
Section: Physical Appearance and Body Imagementioning
confidence: 99%
“…This is in contrast to the long standing “What is Beautiful is Good” bias ( Dion et al, 1972 ). From a recent study using fMRI, it appears that these negative responses are “hardwired” into the occipito-temporal cortex as well as anterior cingulate cortex of the brain ( Hartung et al, 2019 ), which may explain the particularly negative reactions that facial disfigurement illicits ( Stone and Potton, 2019 ; Rasset et al, 2022 ). Encouragingly, plastic surgical procedures that minimize disfigurement result in more positive perceptions of individuals with disfigurement ( Mazzaferro et al, 2017 ; Jamrozik et al, 2019 ).…”
Section: Physical Appearance and Body Imagementioning
confidence: 99%
“…The results showed that, when high anonymity was guaranteed, participants reported more sorrow and curiosity, less positive and more negative emotions. Based on this, a six-dimension typology describing a wide array of possible affective states experienced by perceivers of people with FD emerged (Rasset et al, 2022b). The dimensions are surprise, anxiety and embarrassment, disgust, hostility, sympathy, and neutral affective states.…”
Section: Affective Reactionsmentioning
confidence: 99%
“…The former engenders automatic and immediate responses which can then be counterbalanced by a more controlled and thoughtful reaction, which occurs slightly later. For this reason, reactions to people with FD often comprise a mixture of negative and positive feelings (Dovidio et al, 2000;Rasset et al, 2022aRasset et al, , 2022b.…”
Section: Ambivalent Reactionsmentioning
confidence: 99%
See 1 more Smart Citation